A Systematic Review of Formative Assessment Tools in the Blended Learning Environment - Febriani, Indah; M. Irsyad Abdullah, M. (International Journal of Engineering and Technology, 2018)
An effective method of student assessment technique is necessary for assessing student knowledge. Nowadays, the utilization of formative assessment tools in blended learning is increasing because it can enhance the learning quality. The main aim of this study to identify and classify existing research through the research approach, assessment tools type, and assessment specialty on formative assessment tools in a blended learning environment. This study guiding the educators in choosing and developing new assessment tools. The methodology of this research using a systematic review. This method using the inclusion and exclusion process to make a systematic review focused and choose appropriate studies. The result shows that the highest usage of assessment tool type is automatic assessment with the percentage of 87%. Semi-Automatic assessment has 13% and manual assessment 0%. It proves that technology is an important part of education and teaching because significantly transform the method of assessment from manual to automatic assessment type. This is a great transformation from the traditional method to the modern method of assessment. We recommend to further improve methods for online formative assessment and develop computer-based testing in a blended learning environment for future work.